Characterization of host defense molecules in the human pancreas. Issue 4 (4th July 2019) - Stenwall, Anton; Ingvast, Sofie; Skog, Oskar; Korsgren, Olle
ABSTRACT: The gut microbiota can play a role in pancreatitis and, likely, in the development of type 1 diabetes (T1D). Anti-microbial peptides and secretory proteins are important mediators of the innate immune response against bacteria but their expression in the human pancreas is not fully known. In this study, immunohistochemistry was used to analyze the expression of seven anti-microbial peptides (Defensin α1, α4, β1-4 and Cathelicidin) and two secretory proteins with known antimicrobial properties (REG3A and GP2) in pancreatic and duodenal biopsies from 10 non-diabetic organ donors and one organ donor that died at onset of T1D. Immunohistochemical data was compared with previously published whole-transcriptome data sets. Seven (Defensin α1, β2, β3, α4, GP2, Cathelicidin, and REG3A) host defense molecules showed positive staining patterns in most non-diabetic organ donors, whereas two (Defensin β1 and β4) were negative in all non-diabetic donors. Two molecules (Defensin α1 and GP2) were restricted to the exocrine pancreas whereas two (Defensin β3, α4) were only expressed in islet tissue. Cathelicidin, β2, and REG3A were expressed in both islets and exocrine tissue. The donor that died at onset of T1D had generally less positivity for the host defense molecules, but, notably, this pancreas was the only one where defensin β1 was found. Neither donor age, immune-cell infiltration, nor duodenal expression correlated to the pancreatic expression of host defense molecules. In conclusion, these findings could have important implications for the inflammatory processes in diabetes and pancreatitis as we find several host defense molecules expressed by the pancreatic tissue.